(untitled) (Foro de Educacion, 2023)
This paper argues that certain fundamental aspects of Paulo Freire’s educational philosophy and pedagogical method should be integrated into a secondary Catholic religious education curricular framework in order to deal successfully with the challenges of the 21st century, focusing on two of Freire’s major works, Pedagogy of the Oppressed and Pedagogy of Freedom. The secondary religious curriculum for the Canadian province of Ontario is used as an example. Particular attention is given to two aspects of Freire’s philosophy and method: the student-centred inquiry process and the life-long process of self-understanding and transformation. The curricular framework itself consists of distinct ‘pillars of knowledge’ that are designed to encompass the entire four-year program of secondary religious education with the students’ knowledge and understanding increasing as they progress through the program. In this paper, Freire’s educational philosophy and pedagogical method are connected to three pillars: the intellectual tradition of inquiry, faith and reason; the living tradition of Church doctrine and teachings; and Christian humanism in the context of contemporary ethical issues.